Pseudo-monocrystalline properties of cylindrical nanowires confinedly grown by electrodeposition in nanoporous alumina templates - Barriga Castro, Enrique Díaz; García, Javier; Mendoza Reséndez, Raquel; Prida, Víctor M.; Luna Criado, Carlos (2017)
Four different cylindrical nanowire systems (nickel, cobalt, Co23Cu77, and multisegmented Co58Ni42/Co83Ni17 nanowires) with single-crystal-like properties were characterized by transmission electron microscopy and selected-area electron diffraction (SAED) under different tilting angles. Although these nanowires have different chemical compositions, crystalline structures and/or diameters, they exhibit similar behaviors, which are unexpected for ideal single-crystals. All the samples presented SAED patterns that did not experience changes from one zone axis to another when the nanowire was tilted in a wide range of angles, exhibiting related apparent interplanar distances that are dependent on the nanowire inclination, yielding deformed patterns that can be unrecognizable. Moreover, face-centered cubic nanowires presented classically forbidden reflections. These behaviors were explained by considering the characteristics of the measurement technique and the confined template-assisted growth, which force the atoms to be accommodated in a cylindrical volume with nanoscale dimensions, yielding the frustrated formation of stable facets and right angles in the nanowire radial directions, together with the formation of stacking faults.